2021
DOI: 10.1016/j.semcdb.2021.04.011
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA regulation of prefrontal cortex development and psychiatric risk in adolescence

Abstract: In this review, we examine the role of microRNAs in the development of the prefrontal cortex (PFC) in adolescence and in individual differences in vulnerability to mental illness. We describe results from clinical and preclinical research indicating that adolescence coincides with drastic changes in local microRNA expression, including microRNAs that control gene networks involved in PFC and cognitive refinement. We highlight that altered levels of microRNAs in the PFC are associated with psychopathologies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 165 publications
2
14
0
Order By: Relevance
“…This work would eventually allow for preventive and therapeutic interventions precisely targeted in time. MicroRNAs, for example, show promise to serve as such markers, as they regulate guidance cue genes in adolescence and are detectable in peripheral fluids (Torres-Berrío et al, 2020b ; Morgunova and Flores, 2021 ). Finally, a critical question that remains open is whether and how “positive” experiences can promote healthy DA system development and improve mental health outcomes in emerging adults.…”
Section: Discussionmentioning
confidence: 99%
“…This work would eventually allow for preventive and therapeutic interventions precisely targeted in time. MicroRNAs, for example, show promise to serve as such markers, as they regulate guidance cue genes in adolescence and are detectable in peripheral fluids (Torres-Berrío et al, 2020b ; Morgunova and Flores, 2021 ). Finally, a critical question that remains open is whether and how “positive” experiences can promote healthy DA system development and improve mental health outcomes in emerging adults.…”
Section: Discussionmentioning
confidence: 99%
“…This is a major health concern due to the potential adverse consequences on brain development, thus rendering the adolescent more vulnerable to addictive and psychopathological disorders (Spear, 2011). Moreover, stress and abuse of substances might exacerbate symptoms associated with psychiatric disorders such as schizophrenia (Thomas and Zakharenko, 2021) and depression (Morgunova and Flores, 2021). This is consistent with the high incidence of mental disorders is high during adolescence.…”
Section: Introductionmentioning
confidence: 82%
“…MicroRNAs are small ncRNAs that regulate messenger RNA (mRNA) translation by binding to the complementary mRNA sequence of target genes. This usually results in reduced gene expression by transcript degradation and/or prevention of mRNA translation, although increased mRNA translation has also been described (Rao and Pack, 2017;Morgunova and Flores, 2021). A single miRNA can bind to multiple mRNA targets resulting in the repression of hundreds of genes, including those coding enzymes involved in other epigenetic processes, as well as a single mRNA can be the target of multiple miRNAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While sensitive periods in sensory systems often occur during very early postnatal development [3][4][5] , we found that adolescence is a sensitive period for mPFC development. Adolescence is known to be a period of vulnerability in the development of psychiatric disorders such as schizophrenia in humans [11][12][13]53 . Moreover, functional imaging studies have shown that thalamo-prefrontal hypoconnectivity, a nding in patients with schizophrenia, is already present in young adolescents at clinical high risk for the disorder 15,18−23 .…”
Section: Adolescence Is a Key Period Of Cortical Maturationmentioning
confidence: 99%